2006
DOI: 10.1080/03079450600817115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental ochratoxicosis in broiler chickens

Abstract: This study describes the toxicity signs that developed when the diet of male broiler chickens was artificially contaminated with different levels of the mycotoxin ochratoxin A (OTA). Chicks were assigned randomly to three groups of 80 chicks that were fed a diet containing 0 parts per billion (ppb) (control, group 1), 400 ppb (group 2) or 800 ppb (group 3) OTA from day 1 to 5 weeks of age. Signs of ochratoxicosis were assessed on the basis of changes in the following criteria: body weight, relative weights of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
78
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 35 publications
27
78
1
5
Order By: Relevance
“…In the present study, the lymphoproliferative response to PHA-P was significantly lower (as compared to Group A) in the chicks kept on OTA-contaminated diets. The finding of our study is in line with results shown by Elaroussi et al (2006) that reported significant decreases in the skin thickness response to PHA-P in male broiler chicks kept on an OTA-contaminated ration (i.e., at 0.4 and 0.8 mg/Kg diet) for 5 weeks. The significant decrease in the thymus weight and depletion of lymphoid cells noted here-and also reported earlier by Elauorssi et al (2006), Al-Anati andPetzinger (2006), andDwividi andBurns (1985)-provide significant clues to allow us to better understand the depression in T-lymphocyte functions in OTA-treated birds.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the lymphoproliferative response to PHA-P was significantly lower (as compared to Group A) in the chicks kept on OTA-contaminated diets. The finding of our study is in line with results shown by Elaroussi et al (2006) that reported significant decreases in the skin thickness response to PHA-P in male broiler chicks kept on an OTA-contaminated ration (i.e., at 0.4 and 0.8 mg/Kg diet) for 5 weeks. The significant decrease in the thymus weight and depletion of lymphoid cells noted here-and also reported earlier by Elauorssi et al (2006), Al-Anati andPetzinger (2006), andDwividi andBurns (1985)-provide significant clues to allow us to better understand the depression in T-lymphocyte functions in OTA-treated birds.…”
Section: Discussionsupporting
confidence: 93%
“…A similar effect on broiler chick immune system organ weights-due to ochratoxicosis-was reported by Dwivedi and Burns (1984), Hanif et al (2008), and Awaad et al (2011). Feeding an OTA-contaminated (0.4 and 0.8 mg/Kg diet) diet to male broiler chicks from the day after hatching to 5 weeks-of-age resulted in the significant decrease in thymus weight (Elaroussi et al, 2006). This effect of OTA may be attributed to cytotoxic and degenerative changes in the lymphoid follicles (Al-Anati and Petzinger, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Ochratoxins cause signiicant health problems and economic losses in poultry [26] and cause mycotoxic porcine nephropathy (MPN) [27]. Ochratoxin-related diseases are characterized by severe kidney damage, which could be overtly related to the exposure to ochratoxins, sometimes in combination with diferent mycotoxins [27].…”
Section: Ochratoxinsmentioning
confidence: 99%
“…Os efeitos tóxicos incluem nefrotoxicidade, hepatotoxicidade (KUIPPER-GODMAN; SCOOT, 1989), teratogenicidade (WANGIKAR et al, 2004), imunotoxicidade (ELAROISSE et al, 2006) e carcinogenicidade. Além disso, é classificada como possivelmente carcinogênica para seres humanos (categoria 2B) pelo IARC (1993).…”
Section: Efeitos Tóxicológicos Em Avesunclassified
“…Frangos de corte alimentados com ração artificialmente contaminada com OTA (800 µg Kg -1 ) durante cinco semanas, apresentaram redução do peso corpóreo, do consumo de ração, além de diminuição da taxa de conversão alimentar e aumento da mortalidade (ELAROISSE et al, 2006). Sakthivelan e Rao (2010) contaminaram rações destinada a frangos de corte com OTA em concentrações de 1000 a 2000 µg Kg -1 e também relataram redução da taxa de crescimento, da ingestão de ração, da conversão alimentar, além da redução de proteínas séricas e albumina.…”
Section: Efeitos Tóxicológicos Em Avesunclassified